Cognitive competencies and learning objects - Malbrán, María del Carmen (2006)
The purpose of this paper is reporting an experience of designing digital learning objects for university teaching. The tasks consisted of participating in an electronic forum and developing teaching projects using simulation as a didactic tool. Both were mediated by the computer. They took place in a postgraduate seminar. The participants were university teachers and researchers from diverse areas – sciences, literature, arts and technology, performing varied academic tasks: teaching, research, consultation, and training. Attendees were assisted via e - mail and by direct tutoring while participating in the discussion list and developing the projects, adopting a model of action – research. Participants were asked to propose issues that could be discussed on - line. They chose three : 1.Is a digital mind or a digital intelligence conceivable? If so, how can we identify its traits? 2.Are creativity and digital learning contradictory or complementary processes? 3.How can electronic plagiarism in academic and research work be identified? The themes were discussed one at a time in three courses. Electronic simulation devices covered different subjects according to the discipline of the authors. The resulting projects were presented to teachers, tutors and peers in a collaborative atmosphere and evaluated by a checklist.